THE RELATIONSHIP BETWEEN THE INCIDENT OF IMPACTED TOOTH CASES WITH THE PATIENT’S MOTIVATION TO DO ODONTECTECTOMY TREATMENT AT RSKGM FKG UI - Irawan, Erwin (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Background: Impacted teeth are tooth growth that is blocked by the growth of teeth in the jaw arch because they are obstructed by adjacent teeth or buried by soft tissue. Impacted teeth often occur in third molars, followed by canines. The prevalence of impacted third molars is quite high, reaching 96.56%. Impacted teeth are performed using an extraction procedure called odontectomy. The public must have the motivation to carry out odontectomy if there are complaints about impacted teeth. Objective: To determine the relationship between the incidence of impacted tooth cases and patient motivation to undergo odontectomy at RSKGM FKG UI in 2023. Method: Analytical research with a cross sectional approach. A sample of 50 patients who visited RSKGM FKG UI in the oral surgery room for the period September 2023. The tool for measuring the incidence of impacted teeth uses a recapitulation form and patient motivation using a questionnaire. Results: The majority of cases of impacted teeth were in class II (76%), most of the patients' motivation for undergoing odontectomy was good (70%). There is a significant relationship between the incidence of impacted teeth and the patient's motivation to undergo odontectomy because the p-value is 0.000. Conclusion: Impacted teeth on average occur in women aged 21-30 years with a class II classification.